2016
DOI: 10.1038/srep35005
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between HLA class II alleles and antigens with gestational diabetes mellitus: A meta-analysis

Abstract: Gestational diabetes mellitus (GDM) is defined as glucose intolerance with onset or first recognition during pregnancy. It is associated with an increased risk of pregnancy complications. Susceptibility to GDM is partly determined by genetics and linked with type 1 diabetes-associated high risk HLA class II genes. However, the evidence for this relationship is still highly controversial. In this study, we assessed the relationship between HLA class II variants and GDM. We performed meta-analysis on all of lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Several immune‐related genes were hypermethylated and dysregulated expressed in visceral omental adipose tissue in the GDM group compared with controls . Furthermore, downregulation of both MHC class I genes and MHC class II genes were found in GDM, and GDM susceptibility is known to be associated with HLA class II genes in type 1 diabetes . However, further studies are needed to explain how HLA‐F contributes to GDM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Several immune‐related genes were hypermethylated and dysregulated expressed in visceral omental adipose tissue in the GDM group compared with controls . Furthermore, downregulation of both MHC class I genes and MHC class II genes were found in GDM, and GDM susceptibility is known to be associated with HLA class II genes in type 1 diabetes . However, further studies are needed to explain how HLA‐F contributes to GDM pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…HLA‐DPA1 , another under‐expressed gene, has been reported to signally enhance the risk of developing T1DM. Interestingly, Guo et al performed a meta‐analysis of GDM risk and HLA class II mutations ( DQB1 and DRB1 ), finding that DQB1 *02 and DRB1 *1302 were related to elevated risks for progression to GDM 26 . Therefore, it can be inferred that four HLA class II variants ( HLA‐DQA1 , HLA‐DRB1 , HLA‐DPA1, and HLA‐DQB1 ) were probably involved in the molecular mechanisms of GDM progression.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, there are growing evidence suggesting that GDM is also associated with type I diabetes, which is a chronic autoimmune disease concerned with the immunemediated injury of pancreatic β-cells and the compromised endogenous insulin production. 29,30 Therefore, identification of more molecular biomarkers that are shared by GDM and both types of diabetes will be helpful for understanding as well as diagnosing GDM. In this study, we found that the key players in the regulatory network of DEG profiles were products encoded by the HLA class II genes, which are responsible for producing self-antigens and regulating autoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…GDM was originally regarded as a risk factor for developing type II diabetes . However, there are growing evidence suggesting that GDM is also associated with type I diabetes, which is a chronic autoimmune disease concerned with the immune‐mediated injury of pancreatic β‐cells and the compromised endogenous insulin production . Therefore, identification of more molecular biomarkers that are shared by GDM and both types of diabetes will be helpful for understanding as well as diagnosing GDM.…”
Section: Discussionmentioning
confidence: 99%